2015
DOI: 10.1016/j.ab.2014.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Identification of oxidized phospholipids in bronchoalveolar lavage exposed to low ozone levels using multivariate analysis

Abstract: Chemical reactions with unsaturated phospholipids in the respiratory tract lining fluid have been identified as one of the first important steps in the mechanisms mediating environmental ozone toxicity. As a consequence of these reactions, complex mixtures of oxidized lipids are generated in the presence of mixtures of non-oxidized naturally occurring phospholipid molecular species, which challenge methods of analysis. Untargeted mass spectrometry and statistical methods were employed to approach these complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 31 publications
1
16
0
Order By: Relevance
“…Although formation of oxysterols following exposure to O 3 has been shown before (28,35), whether and how these O 3 -derived oxysterols can form oxysterol-protein adducts in the context of O 3 exposure in the human airway has not been examined. Assays based on "click" cyclo-addition methods make it possible to visualize protein-lipid adducts via immunostaining and to determine protein adductions with specific signaling molecules, thus providing novel insight into the mechanisms behind O 3 -induced adverse health effects (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although formation of oxysterols following exposure to O 3 has been shown before (28,35), whether and how these O 3 -derived oxysterols can form oxysterol-protein adducts in the context of O 3 exposure in the human airway has not been examined. Assays based on "click" cyclo-addition methods make it possible to visualize protein-lipid adducts via immunostaining and to determine protein adductions with specific signaling molecules, thus providing novel insight into the mechanisms behind O 3 -induced adverse health effects (39).…”
Section: Discussionmentioning
confidence: 99%
“…Rodent exposure studies and in vitro studies using human pulmonary surfactant have demonstrated the formation of O 3 -derived oxidized cholesterol products in various chemical compositions (5,6,10,27,28). Fig.…”
mentioning
confidence: 99%
“…Several pro-oxidant exposures have now been shown to drive the formation of oxPLs in pulmonary surfactant (Figure 2). In vitro exposure of human BALF to ozone directly induces multiple PC and PG oxidation products (4). In vivo exposure of mice to a wide variety of airway challenges, including cigarette smoke, particulate matter 2.5, acid, H1N1 influenza A virus, and H5N1 avian influenza virus also increases oxPAPC species and 1-palmitoyl-2-(9'-oxo-nonanoyl)glycerophosphocholine (PON-GPC) in airspace fluid (73)(74)(75)(76)(77).…”
Section: Oxidized Surfactant Phospholipids: Ancient Neolipids With a mentioning
confidence: 99%
“…A large body of evidence has reported elevated levels of MDA, 4HNE or Ox-PLs or their corresponding protein adducts in the bronchoalveolar lavage fluid, lung tissue and/or serum of patients with various lung diseases such as asthma, COPD, ARDS and IPF [43,[64][65][66]. Immunohistochemical analysis revealed greater accumulation of 4HNE in the airways, alveolar epithelium and inflammatory cells of the lungs of COPD patient when compared to smoker non-COPD patient with similar smoking history [67].…”
mentioning
confidence: 98%